Pengembangan Aplikasi Android Sebagai Media Pembelajaran pada Materi Bentuk Molekul untuk Kelas XI SMA/MA - Cici Nur Awida; Fajriah Azra (G-Tech: Jurnal Teknologi Terapan, 2024)
The purpose of this research is to develop a product in the form of an android application on molecular shape material for class XI SMA / MA which is valid and practical. This type of research is research the Plomp development model which consists of three stages of research, namely preliminary research, prototyping and assessment phase. This research is limited to the small group practicality stage. The validity test was conducted by four chemistry lecturers from FMIPA, UNP as material and media experts, two lecturers from FT, UNP as media experts and two teachers from SMAN 9 Padang as material experts. Practicality was conducted on two teachers and twelve students. The validity analysis technique uses Aiken's V index and the practicality technique uses the percentage formula. The findings demonstrated that while the small group practicality prAoduced very practical results (the percentage value of practicality was 90,36% for teachers and 87,02% for students), the android application as a learning medium developed was classified as valid (obtained an average value of 0.90 for material experts and 0.92 for media experts).